Preoperative myocardial fibrosis is associated with worse survival after alcohol septal ablation in patients with hypertrophic obstructive cardiomyopathy: A delayed enhanced cardiac magnetic resonance study - Chen, Youzhou; Zhao, Xingshan; Yuan, Jiansong; Zhang, Yan; Liu, Wei; Qiao, Shubin (Frontiers in Cardiovascular Medicine, 2022)
Background: Prior studies have shown that myocardial fibrosis can be detected by late gadolinium enhancement (LGE) of cardiac magnetic resonance (CMR) and might be associated with an increased mortality risk in hypertrophic cardiomyopathy (HCM). The objective of this study was to examine the prognostic utility of LGE in patients with hypertrophic obstructive cardiomyopathy (HOCM) undergoing alcohol septal ablation (ASA). Materials and Methods: We conducted a retrospective study that consisted of 183 consecutive patients with symptomatic drug-refractory HOCM who underwent CMR for the assessment of myocardial fibrosis before ASA. Cardiovascular disease-related survival was evaluated according to LGE-CMR status. Results: The cohort comprised 74 (40.4%) women with a mean age of 51 ± 8 years. Preoperative myocardial fibrosis was detected in 148 (80.9%) patients. After a median of 6 years (range 2 to 11 years) of follow-up, adverse clinical events occurred in 14 (7.7%) patients. Multivariate-adjusted Cox regression analyses revealed that age [hazard ratio (HR) 1.142 (1.059-1.230), p = 0.001] and LGE [HR 1.170 (1.074-1.275), p < 0.001] were independent predictors of cardiovascular mortality during follow-up. Conclusion: Preoperative myocardial fibrosis measured by LGE-CMR was an independent predictor of increased adverse clinical outcomes in patients with HOCM undergoing ASA and could be used for the preoperative evaluation of risk stratification and long-term prognosis after ASA in these patients.